2021
DOI: 10.1080/14787210.2021.1909476
|View full text |Cite
|
Sign up to set email alerts
|

System for administering and monitoring hydroxychloroquine prophylaxis for COVID-19 in accordance with a national advisory: preliminary experience of a tertiary care institute in India

Abstract: Background Hydroxychloroquine (HCQ) was one of the earliest drugs to be recommended for tackling the COVID-19 threat leading to its widespread usage. We provide preliminary findings of the system, established in a tertiary care academic center for the administration of HCQ prophylaxis to healthcare workers (HCW) based on Indian Council of Medical Research (ICMR) advisory. Methods A dedicated clinical pharmacology and internal medicine team screened for contraindications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…17 Another observational study from India where HCQ was used as prophylaxis against COVID-19, has not shown abnormal QTc duration. 18 All three cases might be just the tip of the iceberg. Because of the lack of CO-oximetry at several centers, the actual incidence of to cefoperazone-sulbactam.…”
Section: Discussionmentioning
confidence: 99%
“…17 Another observational study from India where HCQ was used as prophylaxis against COVID-19, has not shown abnormal QTc duration. 18 All three cases might be just the tip of the iceberg. Because of the lack of CO-oximetry at several centers, the actual incidence of to cefoperazone-sulbactam.…”
Section: Discussionmentioning
confidence: 99%